Prefusion-specific antibody-derived peptides trivalently presented on DNA-nanoscaffolds as an innovative strategy against RSV entry - Issmail, Leila; Möser, Christin; Jäger, Christian; Altattan, Basma; Ramsbeck, Daniel; Kleinschmidt, Martin; Buchholz, Mirko; Smith, David; Grunwald, Thomas (Frontiers in Virology, 2022)
Human respiratory syncytial virus (RSV) is the primary cause of acute lower respiratory tract infections in children and the elderly worldwide, for which neither a vaccine nor an effective therapy is approved. The entry of RSV into the host cell is mediated by stepwise structural changes in the surface RSV fusion (RSV-F) glycoprotein. Recent progress in structural and functional studies of RSV-F glycoprotein revealed conformation-dependent neutralizing epitopes which have become attractive targets for vaccine and therapeutic development. As RSV-F is present on viral surface in a trimeric form, a trivalent binding interaction between a candidate fusion inhibitor and the respective epitopes on each of the three monomers is expected to prevent viral infection at higher potency than a monovalent or bivalent inhibitor. Here we demonstrate a novel RSV entry inhibitory approach by implementing a trimeric DNA nanostructure as a template to display up to three linear peptide moieties that simultaneously target an epitope on the surface of the prefusion RSV-F protein. In order to design synthetic binding peptides that can be coupled to the DNA nanostructure, the prefusion RSV-F-specific monoclonal antibody (D25) was selected. Complementarity-determining region 3 (CDR3) derived peptides underwent truncation and alanine-scanning mutagenesis analysis, followed by systematic sequence modifications using non-canonical amino acids. The most effective peptide candidate was used as a binding moiety to functionalize the DNA nanostructure. The designed DNA-peptide construct was able to block RSV infection on cells more efficiently than the monomeric peptides, however a more moderate reduction of viral load was observed in the lungs of infected mice upon intranasal application, likely due to dissociation or absorption of the underlying DNA structure by cells in the lungs. Taken together, our results point towards the inhibitory potential of a novel trimeric DNA-peptide based approach against RSV and open the possibility to apply this platform to target other viral infections.